Recycle Household Waste For Resident of Karang Tengah Village Bogor West Java - Heni Widyaningsih (Jurnal Pemberdayaan Masyarakat Madani (JPMM), 2021)
Several local government agencies have made efforts to empower the community in the use of householdwaste, however, due to the vastness and complexity of internal problems resulting not all areas can be reached. The State University of Jakarta requires lecturers to carry out community service or Pengabdian Kepada Masyarakat (PKM) every year. The purpose of PKM is to provide understanding, skills, and enrichment to the community to utilize household waste so that residents of Karang Tengah Village, Bogor, West Java can play an active role in creating economic independence for residents by utilizing waste with the 3R concept (Reuse, Reduce and Recycle). This activity was held on Monday, September 28, 2020, at the Head Office of Karang Tengah Village, Babakan Madang District, Bogor, West Java. The activity was opened by representatives from the Sub-district and attended by around 50 participants. The output of this activity was the publication in the PosKota and Suara Karya ewspapers on October 3, 2020, the Activity Poster, and the Tutorial Video on Making Candles from Used Cooking Oil.